Generative AI Solutions for Creative and Enterprise Applications Unlocking New Possibilities - Venkateswara Rao Batta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Generative AI has emerged as a transformative technology, reshaping creative and enterprise landscapes. This paper presents an advanced framework for developing generative AI solutions tailored to diverse applications, including content creation, design automation, and enterprise decision-making. By leveraging cutting-edge Large Language Models (LLMs) and multimodal AI techniques, the proposed system achieves exceptional versatility and creativity. Case studies in marketing, product design, and customer engagement highlight significant productivity gains and enhanced user experiences. The study emphasizes the transformative potential of generative AI in driving innovation across industries while addressing ethical and operational challenges.